Positive effects of Mulberry leaf extract on egg quality, lipid metabolism, serum biochemistry, and antioxidant indices of laying hens - Zhang, Bo; Wang, Zeben; Huang, Chenxuan; Wang, Dehe; Chang, Dongmei; Shi, Xiaowei; Chen, Yifan; Chen, Hui (Frontiers in Veterinary Science, 2022)
Plant extracts are becoming a hot topic of research by animal husbandry practitioners following the implementation of a global policy to restrict antibiotic use in animal production. Mulberry leaf extract has received considerable attention as a new plant extract. Mulberry leaf polysaccharides and flavonoids are its main constituents, and these substances possess immunoregulatory, hypoglycemic, antioxidant, and anticoagulant properties. It is however less common to use them in poultry production. Therefore, we investigated the effects of adding MLE to the diet of laying hens on egg quality, lipid metabolism, serum biochemistry, and antioxidant indices in this study. A total of 288 Lohmann Silber layers, aged 38 weeks, were randomly assigned to four groups (six replicates of 12 hens each). Hens were fed a basal diet supplemented with 0 (control diet), 0.4, 0.8, or 1.2% MLE for 56 d. Results showed that the addition of 0.4–1.2% MLE to the diet improved aspartate transaminase (AST) activity in the serum of laying hens, reduced low-density lipoprotein (LDL-C) content in the serum, and significantly decreased yolk triglyceride (TG) and total cholesterol (TC) contents (P < 0.05). No adverse effects were observed on production performance (P > 0.10). MLE (0.4 and 1.2%) significantly reduced the TG and TC levels in the liver (P < 0.05). MLE (0.8 and 1.2%) significantly increased glutathione peroxidase (GSH-Px) activity in the serum, decreased alanine transaminase (ALT) activity, TG and TC content in the serum, and improved egg yolk color (P < 0.05). MLE (1.2%) significantly increased high-density lipoprotein (HDL-C) content and superoxide dismutase (SOD) activity in the serum and enhanced eggshell strength (P < 0.05). The liver-related lipid metabolism gene assay revealed that the relative mRNA expression of PPARα and SIRT1 in the liver was significantly upregulated and that of FASN and PPARγ was significantly decreased after the addition of MLE. In contrast, the relative mRNA expression of SREBP-1c in the liver dramatically decreased after the addition of 0.8 and 1.2% MLE (P < 0.05). The addition of MLE to the diet improved egg quality and the economic value of hens by increasing antioxidant capacity and lipid metabolism. The most appropriate amount of MLE to be added to the diet of laying hens was 0.8%. Our study provides a theoretical reference for the application of MLE in egg production and to promote the healthy and sustainable development of the livestock and poultry industry under the background of antibiotic prohibition.